(untitled) (Research, Society and Development, 2020)
The objective was to list the main diagnoses, results and nursing interventions for the frail elderly in a Long-Term Institution and for elderly people at home affected by the new coronavirus (COVID-19). This is a document review study, with a qualitative approach, of a descriptive and exploratory nature developed based on the official documents published by the Ministry of Health and on the documents prepared and published by the Brazilian Nursing Association through the Scientific Department of Gerontological Nursing, in the Research Network in Nursing Processes. Nursing (RePPE). The collection took place in June 2020, that aimed to answer the following guiding question: What are the diagnoses, results and nursing interventions for the frail elderly, affected by COVID-19 at home and institutionalized? Eleven nursing diagnoses and respective results and interventions were identified for frail elderly people in long-term care facilities and also 11 for elderly people at home. The importance of using taxonomy to systematize the assistance of nurses is evidenced, mainly to consider this group vulnerable, aiming to facilitate the development of strategies and nursing prescriptions that can subsidize nursing care for those elderly.